2017
DOI: 10.1080/14737175.2017.1395700
|View full text |Cite
|
Sign up to set email alerts
|

ROCK as a therapeutic target for ischemic stroke

Abstract: Introduction: Stroke is a major cause of disability and the fifth leading cause of death. Currently, the only approved acute medical treatment of ischemic stroke is tissue plasminogen activator (tPA), but its effectiveness is greatly predicated upon early administration of the drug. There is, therefore, an urgent need to find new therapeutic options for acute stroke. Areas covered: In this review, we summarize the role of Rho-associated coiled-coil containing kinase (ROCK) and its potential as a therapeutic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 101 publications
0
25
0
5
Order By: Relevance
“…Fasudil and Y27632 are widely used nonselective ROCK inhibitors. These inhibitors target ROCK's ATP-dependent kinase domain and are equipotent in inhibiting both isoforms [17]. Due to these limitations and the nonselectivity of ROCK inhibitors, fasudil is the only ROCK inhibitor approved for human use in Japan and Quantitative analysis of the number of surviving neurons from ICH and ICH/HF rat brains in the perihematomal area at each time point.…”
Section: Discussionmentioning
confidence: 99%
“…Fasudil and Y27632 are widely used nonselective ROCK inhibitors. These inhibitors target ROCK's ATP-dependent kinase domain and are equipotent in inhibiting both isoforms [17]. Due to these limitations and the nonselectivity of ROCK inhibitors, fasudil is the only ROCK inhibitor approved for human use in Japan and Quantitative analysis of the number of surviving neurons from ICH and ICH/HF rat brains in the perihematomal area at each time point.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, an important mechanism was revealed as miR-335 was observed to regulate SG formation by targeting the mRNA of ROCK2. Bioinformatics analysis predicted that ROCK2 mRNA is targeted by miR-335 and ROCK2 served an important role in ischemic stroke (45,46). ROCKs can lead to the phosphorylation of downstream substrates and induce alterations in cellular function.…”
Section: Discussionmentioning
confidence: 99%
“…ROCK modulates actin filament assembly resulting in force generation and cell adhesion, migration and phagocytosis. The activation of ROCK is also involved in the contraction of the actomyosin ring and in the intermediate filaments disorder during cytokinesis [ 26 , 27 ]. Besides the assembly of F-actin stress fibers, ROCK also mediates the release of transcription factors such as myocardin-related transcription factor (MRTF) and yes-associated protein (YAP), promoting changes in gene expression and phenotypic changes [ 26 , 27 ].…”
Section: Overview On Rock Structure and Functionsmentioning
confidence: 99%